Efeito neuroprotetor da toxina Ph 1 recombinante no trauma medular agudo em ratos - Maria Paula Rajao Costa Coelho (2016)
Spinal cord injury is a common disease in human and veterinary medicine, with serious consequences for the one affected and for society. It causes damage to the nervous tissue by primary and secondary mechanisms, being exacerbated influx of calcium, mainly due to the activation voltage-dependent calcium channels, a secondary event considered critical in the pathogenesis of spinal cord injury. The Ph1 peptide obtained from the purification of the whole venom of Phoneutria nigriventer spider is able to block voltage-dependent calcium channels and thereby reduce calcium influx. This study aimed to evaluate the effect of intrathecal administration of different doses of recombinant Ph1 toxin in spinal cord experimentally injured rats. Thirty male Wistar rats were randomly distributed into five groups. Animals belonging to CN group underwent dorsal laminectomy. In other groups, beyond laminectomy, animals underwent acute spinal cord contusive trauma. Animals belonging the control groups received placebo intrathecally administered and treated animals received 25, 50 e 100 pmol of the toxin by the same via. Forty-eight hours after surgery animals were euthanized and were collected blood and urine samples, besides and spinal cord segments, for reactive oxygen species and lipid peroxidation quantification and to assess gene expression of apoptosis- related genes by qRT-PCR. It showed reduction in lipid peroxidation in all three groups who had received the toxin, wich suggests neuroprotector effect.